Automatic measurement of rail line expansion joint gaps - Islam, Samiul; Khan, Rubayat Ahmed; Biswas, Rubel (© 2014 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the IEEE International Conference on Vehicular Electronics and Safety, ICVES 2014; Hyderabad; India; 16 December 2014 through 17 December 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICVES.2014.7063720